Synthesis and Spectroscopic Characterization of Some Novel Schiff Base Complexes of Transition Metals and Their Biological Studies - Pal Singh, Netra; Saini, Poonam; Kumar, Asvini (Asian Journal of Chemistry, 2014)
Cobalt(II) and manganese(II) complexes of novel Schiff base derived from 4,5-dimethoxy-1,2-phenylenediamine and 5-substituted salicylaldehyde have been synthesized and characterized by various physico-chemical techniques viz. elemental analysis, magnetic moment, IR, NMR and electronic spectral studies. The complexes have been found to have a stoichiometry of 1:1 (M:L). The probable geometry and biological activity of the complexes also have been reported.